INVESTIGATION OF RELIGIOUS VALUES IN BUILDING DIVERSITY ATTITUDE OF HIGH SCHOOL STUDENTS IN THE MODERN ERA - Nurdiyanto, Nurdiyanto; Muhammad Polem; Ningsih, Nur Wahyu; Hermawan, A Heris; Hasan Basri; Suhartini, Andewi (LP2M IAI Al-Khairat Pamekasan, 2024)
The aim of this research is to analyze and examine in depth how the instillation of religious values contributes to developing the religious attitudes of high school students and the challenges faced in forming the religious attitudes of high school students in the modern era. Meanwhile, the approach taken in this research uses a qualitative approach with the library research method. The data source for this research combines two primary and secondary sources. Primary media include journal articles, e-books, websites, and other internet media. Meanwhile, secondary sources include online proceedings, magazines, newspapers, and other sources related to the discussion theme. The data collection techniques collect the sources that have been mentioned, classify them, and then draw conclusions. Meanwhile, what is used in this research is a descriptive analysis technique, namely by integrating general knowledge, then drawing specifically (inductively) based on the results of literature findings, which have been carried out with the stages of collecting secondary and primary data, then classifying the data, displaying the data, and then interpreting it to produce knowledge for drawing. conclusion. The results of the research found that instilling religious values in developing students' religious attitudes includes: (1) the role of educators in instilling religious values; (2) the challenges of religious attitudes in the modern era; (3) the implementation of a religious values instillation program; (4) the relationship between religious attitudes and technological developments; and (5) the influence of the school environment in forming religious attitudes. So it can be concluded that the value of worship, the value of the spirit of jihad, the value of morals, the value of example, and the value of trust and sincerity of these five are the core values of the religious values as the basis.